Unintentional transvesical caesarean section: incidence, risk factors, surgical technique and post-operative management. (May 2019) - Franchi, Massimo; Raffaelli, Ricciarda; Baggio, Silvia; Scollo, Matteo; Garzon, Simone; Laganà, Antonio Simone; Casarin, Jvan; Zanconato, Giovanni; Cromi, Antonella; Ghezzi, Fabio
Abstract: Objective(s): To assess incidence, risk factors, management, and short and long-term outcomes of unintentional transvesical caesarean section (UTV-CS) defined as any extraction of the fetus through a double full thickness bladder wall cystotomy. Study design: Data about all UTV-CS between January 2013 and December 2017 were retrieved searching the diagnosis of bladder injury and bladder repair during caesarean section (CS) in our comprehensive computerized labor and delivery database and register. CS with bladder wall injury not classified as UTV-CS were excluded. Data analysis included maternal history, demographics and obstetric parameters, details regarding CSs, bladder injury location and extension, and short- and long-term maternal outcomes. Results: Among 28, 822 deliveries, 7, 616 (26.42%) were CSs. Three cases of UTV-CS were identified with comprehensive incidence of 0.039%. We provided details of the reported cases and described bladder repair procedure. Conclusion(s): This is the first study that assessed the incidence of UTV-CS. UTV-CS risk factors are consistent with factors related to milder bladder injuries. The risk of bladder injury during CS should be always considered, despite the low incidence of this complication. Prompt diagnosis and surgical repair seem to allow avoiding severe complications and recovery of a normal urological function even in UTV-CS.